Social capital as a measure of innovation for rural clusters: the case of France and US - Ion Lucian Ceapraz (European Regional Science Association (ERSA), 2012)
The paper emphasizes the role of social capital in some particular rural clusters like the French "Poles d'Excellence Rurale" (PER) and the U.S. Rural Knowledge Clusters (RKC). The recent revival of the literature on social capital considers this resource as highly valuable when considering the development of rural clusters. The purpose of our paper is to investigate the various mechanisms of social capital that can release the economic development of these areas. Through bilateral comparisons we are interested in how differences and similarities in social structures between the PER and the RKC may affect rural growth and competitiveness. There is a growing literature on the correlation between social capital variables and important economic outcomes (Glaeser et al., 2002). We do not intend to investigate how is created the social capital in the rural areas but to underline the ongoing effects of social capital that made these PER and RKC such a successful story. In our opinion, their performance and outcomes are highly dependent on the type of social capital which is expected to contribute to the cooperation and innovation (Staber, 2007) of these rural clusters. According to Staber (2007) some recent OECD papers outline that "there is no one model of social capital and no one type of impact on cluster performance" (OECD, 2002). An increased interest from political institutions in developing specific tools in starting and maintaining the role of social capital as an important resource is unveiled in recent years in these rural areas. The development of this resource at the individual and community levels is the ultimate goal of sustainable rural development (Dwyer, Findeis, 2008). The tools employed by public and private institutions in Europe and US differ substantially regarding the role of institutions but are commonly similar to the output of rural growth. One important aspect affecting the type of social capital in these rural areas concerns the increasing importance of urbanization and the proximity of rural and urban areas. In this aspect as our paper reveals the French rural areas seem quite different concerning their "rurality" compared with the US counterparts.
Keywords: R10; R11; R12; 330; "Poles d'Excellence Rurale"; US Rural Kowledge Clusters; Social Capital; Innovation